OPHTHALMOLOGY: YESTERDAY, TODAY AND TOMORROW - Bilalov, Erkin; Oripov, Okilkhon (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The filling of the piggy bank of scientific knowledge concerning new aspects of etiopathogenesis, diagnostic methods, medical and surgical treatment of eye diseases is not interrupted for a single day. External circumstances, including the epidemiological situation in which we currently live, can only complicate, but in no way stop this process. One of the immutable postulates of ophthalmology, as, indeed, of the entire medical specialty, is the need for continuous improvement of a specialist doctor based on the exchange of accumulated information and the implementation of the experience gained in clinical practice.